Present status of pond fishery resources and livelihood of the fish farmers at Mohanpur Upazila in Rajshahi District - Zaman, Tanjeena; Jewel, MAS; Bhuiyan, AS (University Journal of Zoology, Rajshahi University, 2007)
A survey was conducted in Mohanpur Upazila, Rajshahi to determine the pond fishery resources and the livelihood status of fish farmers for a period of nine months (August 2005-April 2006). The survey was conducted on 90 fish farmers of 52 villages under 6 unions. Data were collected through personal visit and interviews following a detailed questionnaire. Pond sizes of the area varied from 15 to above 180 decimal of which maximum ponds (57.8%) were operated by single owner. Field observation revealed that 65.5% ponds were used for fish culture, whereas 28.5% and 6% ponds were culturable and derelict, respectively. Among the fish farmers 23.3% was illiterate whereas 14.4, 8.9 and 6.7% were educated upto primary, secondary and higher secondary or above level, respectively. Agriculture (51.1%) is the principal occupation of the pond owners followed by aquaculture (18.9%). The highest percentage (33%) fish farmers earned Tk. 25,000-50,000 per year, 32% earned Tk. 50,000-1,00,000 an the rest 25% earned above Tk. 1,25,000 annually. Fish farmers were found to face various problems such as social, economical and technical problems, which were identified during the study. Necessary overcome efforts are also suggested according to the problems. Key words: Pond fishery resources, fish farmers, livelihood status Univ. j. zool. Rajshahi Univ. Vol.25 2006 p.31-35